Ultra-T: UERJBotz's Mini Autonomous Sumo Robot - Rodrigues, Elton de Souza; Santos, Arthur Garcia Luz dos; Braga, Liniker Alves; Revoredo, Téo Cerqueira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
Robotics is a well-established means of project-based approach to create knowledge in areas such as mechanics, electronics, computer science, control and automation, communications and artificial intelligence. At universities, robotics provides ways to expand student abilities beyond those acquired within regular classes and laboratories, stimulating teamwork, critical thinking, creativity, autonomy and entrepreneurial attitude. Robot competitions provide a great way to practice robotics, directing challenges that stimulate students to design different types of robots while enjoying themselves along the way. Among the most popular are sumo robots' competitions. In such context, this paper presents the development of a mini sumo robot capable of competing in both radio-controlled and autonomous categories. It is a result of the work of three undergraduate students based on previous robots designed by UERJ robotics team. Design premises, fabrication and programming details are discussed. Its use on a recent competition evidence project's success not only from a technical point of view, but also from an educational perspective.